Table of Content - -, (Arab Journal for Sciences and Research Publishing, 2023)
Table of Content:1. Mentioning of the Righteous and the Wicked in Surat Al-Mutaffifin in the Quran; An Analytical Rhetorical StudyDr. Meshal Fehan Ballash Al-Osaimi2. The extent of the legitimacy of Arab peace treaties with the Zionist enemy entity in Islamic law and man-made legislationMr. Hameed Aadm Ali Qushaimh3. The effectiveness of an educational unit to develop students' skills in designing fashion shows using virtual reality and its impact on electronic shopping in Asir region, Saudi ArabiaDr. Randa Mounir Elkherbaway, Dr. Samar Ahmed Kanona , Dr. Ngawha Kamel Bosiala4. Introducing innovative designs for horse riding clothing for women in the Kingdom of Saudi ArabiaMrs. Abrar Hashim Alattas , Co-Prof. Hana Abdullah Alamodi5. From natural translation to translation competence: Pedagogical implicationsMrs. Habiba Nakhli6. E-Marketing of Information Services in Yemeni Private University Libraries in Sana'a CityDr. Samar Gamal Al-Habbari
Keywords: Arab Journal of Sciences & Research Publishing